THE IMPORTANCE OF FINANCIAL KNOWLEDGE IN ENHANCING MICROCREDIT AVAILABILITY IN RURAL TANZANIA: INSIGHTS FROM A FINSCOPE HOUSEHOLD SURVEY - Mwita, James (Ayden International Journal of Banking, Finance and Technology, 2024)
Microcredit is essential for providing small loans to rural households in Tanzania, but financial inclusion problems and the structure of the rural credit market make it difficult for these households to access microcredit. This study examines the influence of financial literacy on microcredit accessibility in rural Tanzania using a large dataset from the Finscope household survey. A binary logit estimation technique and descriptive analysis were employed to determine the effects of financial literacy on the credit accessing decisions of rural households. The findings reveal that financial literacy has a negative and significant impact on microcredit accessibility, while education level has a positive and significant influence. The study recommends establishing financial literacy programs in rural areas to educate citizens on the benefits and proper uses of borrowed money. Policymakers and microcredit institutions can use the results to improve microcredit accessibility in rural Tanzania. The study's originality lies in the use of actual surveyed data from Tanzanians in all regions, with robust results that account for different household categories and control variables.